Morbidity and mortality meetings at Australian major trauma centres: A proof of concept study. (October 2018) - Bear, H; Mok, MT; Farrow, N; Curtis, K; Mitra, B; Fitzgerald, M; Gruen, RL
Background: Morbidity and mortality meetings are held at all Australian major trauma centres and provide a forum to identify problems and improve practices. Meetings should focus on addressing factors in the system to prevent similar errors occurring, rather than individual culpability. This paper describes current meeting practices and assesses the use of a systems approach. Methods: This proof of concept study used a convenience sample of four Australian major trauma centres. Trauma leaders at each centre were surveyed regarding morbidity and mortality meeting practices. The use of a systems approach was measured by assessing practices against the London Protocol for Systems Analysis of Clinical Incidents. Meeting participants were also surveyed regarding perceptions of the objectives and effectiveness of meetings. Results: This study found variable utilisation of a systems approach. Cases are not routinely analysed for contributing system factors and effective processes are not always used to correct problems that are identified. Meeting practices also vary between centres in terms of frequency, case selection criteria and use of audit filters. Participants generally view quality improvement as the most important objective of meetings. Conclusion: Morbidity and mortality meeting practices vary between Australian major trauma centres and a systems approach has not been fully adopted.